Biomechanical evaluation of four strand flexor tendon repair techniques, using a double figure of 8 technique - Raghu, Shashank (2018)
Introduction: To determine and biomechanically evaluate the tensile strength, stiffness and mode of failure, of two well established tendon repair techniques, which are the modified Kessler and cruciate technique with the lesser known figure of 8 technique Methodology: Twenty four Achilles tendon of adult chickens were randomized into three groups which were a modified four strand Modified Kessler technique, a four strand cruciate technique, and a double figure of eight technique in order to obtain a four strand core suture. An additional twenty four Achilles tendons of adult chickens were obtained and randomized into the same three groups but with an additional running epitendinous repair. All repairs were performed using a synthetic, non-absorbable, monofilament polypropylene suture material Results: The double figure of eight technique had the highest mean ultimate tensile strength, followed by the modified four strand Modified Kessler technique and the four strand cruciate technique. Analyzing the test with an epitendinous suture significantly affected the results positively. Conclusion: The double figure of eight, four strand suture technique was the strongest and relatively less technically demanding technique to perform in this study. The importance and additional strength provided by epitendinous suture was evident. This may be a clinically acceptable technique to perform in flexor tendon injuries of hand in humans.